TATHBIIIQU MANHAJ 2013 FII TAHSIINI MAKHRAJAAT AT-TA’LIMIYYAH AL-LUGHAH AL-‘ARABIYYAH LISHAF AT-TSAMIN “B” (AL-QUDUS) FII AL-MADRASAH AT-TSANAWIYYAH MAZRO'ATUSSIBYAN CENGAL - Siti Barkah; Asriani; Lukman Taufik Akasahtia (Program Studi Pendidikan Bahasa Arab, 2022)
Curriculum is a container that determines education’s course. For the implementation of the 2013 curriculum stressed competence, knowledge, and skill. Mts Mazroatussibyan Cengal al school implementing the 2013 curriculum in arabic studies. The implementation of curriculum 2013 is expected to increase student’s learning results because this curriculum is essentially centered on students. Teacher only as facilitators and mediators and motivators for student’s, so that students have the spirit of learning and getting better results. The purpose of this study is to describe the implementation, the supporting factors and inhibitors of the 2013 curriculum in improving the results of learning arabic. Using a qualitative approach to case studies. The results of this study may be concluded that the implementation of curriculum 2013 in raising students learning outcomes are properly running, and students learning results have increased during the performances, despite obtacles such as learning resources for deductions, less interesting learning media, passive centering students and lack of discipline in class activities. This needs special attention to achieving the learning purposes consistent with the 2013 curriculums content observing, asking, reasoning, and communicating